Developing and implementing communications strategies: A descriptive model - Loma A. Hill; A. A. Archer (South African Journal of Business Management, 1988)
The world-wide environment, but particularly the South African environment today has created a growing need for businesses to communicate effectively with their stakeholders. The number of stakeholders interacting with companies has burgeoned, their demands have become greater and the need for change is critical. As these pressures increase, the need for companies to communicate effectively will grow. In South Africa the possibility for misunderstanding is compounded by communication barriers such as the socio-political system, diversity of cultures and languages, as well as the many different levels of education. In an environment such as this the need for effective communication is so great that a company can clearly no longer rely on ad hoc, reactive communications to facilitate the achievement of corporate goals. In order to ensure effective communication a company needs to have an overall communications strategy which has its roots in corporate goals and strategies. Developing and implementing communications strategies involves many complex considerations such as the identification and analysis of stakeholders and their power bases, Issues management, corporate image and culture, crisis communications planning, media planning and dealing with communication barriers. This article provides a suggested framework for integrating these and other considerations into the development and implementation of communications strategies.
Keywords: 650